Development of sustainable LSP-Bricks using local industrial wastes / Ani Maslina Saleh, Mohamad Nidzam Rahmat and Norsalisma Ismai - Saleh, Ani Maslina; Rahmat, Mohamad Nidzam; Ismai, Norsalisma (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2021)
Uncontrolled infrastructure development may produce excessive carbon emission and scarcity of natural resources. The reuse of waste materials in general promotes material ecology and the cradle-to-cradle concept. The utilisation of industrial waste in the development of advanced materials promoting the extensive research on sustainable building components. The main objective of this research is to investigate the potential of utilising local industrial waste, Solid Waste Fly Ash (SwFA) and Paint Sludge (PS) as target material in replacing laterite soil that is non-renewable natural resources. Standard industrial size bricks were fabricated consist the combination of Laterite Clay, SwFA and PS (LSP) at 50:25:25 ratios. The results for engineering and environmental properties were within the acceptable of engineering standards and performances. This test result suggests potential used of SwFA and Paint Sludge as substitute to clay for unfired brick. This will certainly contribute to the recycling of SwFA and industrial sludge (Paint Sludge and possibly others) and hence to minimise the impact of these by-product to the environment if send to landfill. The manufacture of unfired bricks can exploit locally available waste materials and can be used in certain applications of low load bearing situation. This research also suggests innovation and enhanced waste management and contribution towards the concept of green building components.